ANALISIS JENIS PENYAKIT PADA TANAMAN KAKAO (Theobroma cacao) DAN TINGKAT SERANGANNYA DI PERKEBUNAN RAKYAT KECAMATAN MOWEWE KABUPATEN KOLAKA TIMUR - Pratiwi, Sindy; Erfina; Kaliu, Sutriani; Tahir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was conducted to identify the types of diseases and pests affecting cocoa plants (Theobroma cacao L.) and to determine the extent of the infestation in smallholder plantations in Mowewe Subdistrict, East Kolaka Regency, Southeast Sulawesi. The research was conducted in April 2026 using a quantitative descriptive approach and field survey methods. A total of 140 cocoa plants located in an area of 0.5 hectares were selected as samples using purposive sampling. The variables observed included the types of diseases and pests, the number of infected plants, and the intensity of infestation. The data were analyzed descriptively, and the intensity of infestation was calculated using the infestation percentage formula. The results of the study revealed that the types of diseases and pests found were fruit rot caused by Phytophthora palmivora, fruit rot caused by Gloeosporium sp., the cocoa fruit borer (Conopomorpha cramerella), and mealybugs. Fruit rot caused by Phytophthora palmivora showed the highest number of infections with 60 infected plants and an infection intensity of 42.85%, which falls into the moderate category. On the other hand, fruit rot caused by Gloeosporium sp. affected 2 plants with an intensity of 1.43%, the cocoa fruit borer affected 14 plants with an intensity of 10%, and mealybugs damaged 3 plants with an intensity of 2.14%, all of which fall into the mild category. These findings indicate that the disease